Efficacy and safety of fasinumab in an NSAID-controlled study in patients with pain due to osteoarthritis of the knee or hip - Stephen J. DiMartino; Haitao Gao; Simon Eng; Guillermo Valenzuela; Thomas Fuerst; Chetachi Emeremni; Tina Ho; Hazem E. Hassan; Kenneth C. Turner; John D. Davis; Souhil Zaim; Jesse Chao; et al. (BMC Musculoskeletal Disorders)
Abstract Objective Osteoarthritis (OA) causes significant musculoskeletal pain. This study assessed the efficacy and safety of fasinumab, an investigational nerve growth factor inhibitor, in patients with moderate-to-severe OA pain of the knee/hip. Methods In this Phase 3, randomized, double-blind, placebo- and non-steroidal anti-inflammatory drug (NSAID)-controlled study, patients with OA (Kellgren-Lawrence grade ≥ 2; Western Ontario and McMaster Universities Arthritis Index [WOMAC] pain score ≥ 4) received (2:1:1:1) fasinumab 1 mg every 4 weeks, diclofenac 75 mg twice daily, celecoxib 200 mg daily, or placebo for 24 weeks. Co‑primary endpoints were change in WOMAC pain and physical function scores to Week 24 versus placebo. For safety, joints were imaged in all patients at pre‑specified times, regardless of symptoms. Results Of 4531 patients screened, 1650 were randomized. At Week 24, greater improvements were observed for fasinumab versus placebo; least-squares mean difference: –0.63 (p = 0.0003) for WOMAC pain and –0.64 (p = 0.0003) for physical function. Improvements were numerically greater for fasinumab versus NSAIDs for physical function (–0.64 versus –0.31; nominal p < 0.05) and pain (–0.63 versus − 0.39; p = NS). Adjudicated arthropathies occurred in 1.6% of placebo-treated, 1.5% of NSAID-treated, and 5.6% of fasinumab-treated patients; joint replacements occurred in 3.6% of placebo-treated, 4.8% of NSAID-treated, and 3.4% of fasinumab-treated patients. Conclusion Fasinumab significantly improved WOMAC pain and physical function scores versus placebo in < 24 weeks in difficult-to-treat patients with pain due to OA of the knee/hip. Adjudicated arthropathies were more frequent with fasinumab; there were no differences in the proportions of patients with joint replacements. Trial registration Clinicaltrials.gov NCT03304379. Date of first registration: October 2, 2017.